BACTERIAL ENDOCARDITIS: CASE REPORT - Dávila F., Roberto (2014)
Bacterial endocarditis is an inflammation of the endocardium, where a bacterialcolonization produces vegetation in the cardiac valve, which can alter its normal functioncausing regurgitations and hemodynamic alterations. Also, this infection can cause septicthromboembolism or inflammatory alterations like immune complexes. The present studydescribes the case of a female canine of 2.5 years of age that presented fever, depression,anorexia and a severe murmur (IV/VI) on the left side of the thorax. Laboratory examsrevealed leukocytosis with left shift and renal failure. Besides, the echocardiography showed vegetation at the aortic valve that altered the hemodynamics producing a diastolicregurgitation jet. It was concluded that the lesion was compatible with bacterial endocar-ditis.